1981
DOI: 10.1136/bmj.282.6259.223
|View full text |Cite
|
Sign up to set email alerts
|

Risks from cannulae used to maintain intravenous access

Abstract: future which do not sequester bacteria in this way. We agree with Oberhammer5 that companies should discontinue manufacturing devices with injection ports which cannot be safely and repeatedly disinfected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Oberhammer (1) and Peters et al (2,3) published reports in 1980/81 indicating that cannula sideports might be a potential risk of contamination in Venflon cannulae. Later reports by MacFarlane et al (4,5) and Cowan (6) did not support the first reports, and our own previous results (7-9) using a special culturing technique showed no correlation between use of the sideport and intraluminal contamination of the cannulae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oberhammer (1) and Peters et al (2,3) published reports in 1980/81 indicating that cannula sideports might be a potential risk of contamination in Venflon cannulae. Later reports by MacFarlane et al (4,5) and Cowan (6) did not support the first reports, and our own previous results (7-9) using a special culturing technique showed no correlation between use of the sideport and intraluminal contamination of the cannulae.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports have dealt with the problem of whether the sideport is a major route of contamination (1)(2)(3)(4)(5)(6). In previous studies we found no correlation between use of sideport and intraluminal contamination of the cannulae (7-9), but in one study we found an intraluminal contamination rate of 16.5% after 4-8 h in use (7), which seems to indicate that the technique of insertion might play a major role in contamination of the intravenous cannulae.…”
mentioning
confidence: 99%